SISTEM PENAMAAN DAN MAKNA PADA MAKANAN TRADISIONAL DI KOTA PADANGSIDIMPUAN - Ilham Sahdi Lubis; Hasian Romadon Tanjung; Hepridayanti . (Institut Pendidikan Tapanuli Selatan, 2021)
This study aims to determine the naming process and meaning of traditional foods in the city of Padangsidimpuan which are connected to five types of traditional foods, so that people can find out the reasons behind the naming of these foods. This type of research is descriptive qualitative using naming based on the characteristics, the similarity of the process of making traditional food and the meaning contained in the food according to its conceptual. Data collection techniques used in data collection are observation, interviews, and documentation. The data analysis technique uses data reduction, data presentation and conclusions. The reduction stage is the provision of data with data collection techniques, namely, documentation in the form of photos and videos. Presentation of data with data analysis. The third stage of verification is to re-examine the data presented so that the results are truly valid. Testing the validity of the data by increasing triangulation. The results of the study of the naming system and meaning of traditional foods in the city of Padangsidimpuan that the five types of traditional foods that have been discussed are taken from the mention of properties, ingredients, and similarity.